KEBERAGAMAN PESERTA DIDIK DALAM PEMENUHAN TARGET KURIKULUM MELALUI PEMBELAJARAN BERDIFERENSIASI - Dina Reski Yani; Rahmi Susanti (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2023)
This study aims to collect various literature reviews and explain concepts related to differentiated learning to fulfill curriculum targets with a diversity of students. Differentiated learning is learning that manages, monitors, assists and directs the activities of students with the diversity of students according to their learning profile, learning readiness and students' interests. The method used in writing this article is a literature review study originating from articles, journals, books, the internet and other literature. The results of the literature review show that the purpose of differentiated learning is to coordinate learning by paying attention to learning interests, learning readiness and learning preferences, accommodating students so that learning objectives can be achieved by all students, increasing motivation and learning outcomes, establishing teacher and student interaction and building attitudes appreciate diversity. The conclusion of differentiated learning can provide opportunities for students to be able to learn efficiently and naturally based on the needs of students with teachers who are able to determine the right methods and approaches.